ANALISIS FAKTOR – FAKTOR SOSIAL EKONOMI YANG MEMPENGARUHI KEUNTUNGAN DAN EFISIENSI PEMASARAN PADA USAHATANI PAPRIKA DI DESA TLOGOSARI KECAMATAN TUTUR - Olyvyatur Rizky; Masyhuri Machfudz; Nikmatul Khoiriyah (Program Studi Agribisnis, 2020)
Tlogosari Village Tutur District is a village that has a lot of natural potential, one of which is paprika. The development of paprika farming is large enough so that this research needs to be done with the aim to analyze efficiently on paprika farming in Tlogosari Village, Tutur Subdistrict, to see socio-economic factors that can affect profits on paprika farming in Tlogosari Village, Tutur District, and identify marketing efficiency paprika farming in Tlogosari Village, Tutur District. The method used in this study is a quantitative method with a purposive location determination and a sample of respondents as many as 33 people whose samples were taken by census. The results obtained from this study showed 1) the results of the R / C ratio showed efficient. 2) socio-economic factors that affect profit by using Unit Output Price (UOP) - Cobb Douglass analysis, namely seed costs, fertilizer costs, drug costs, and labor costs. 3) marketing efficiency in paprika farming in Tlogosari village, Tutur sub-district was declared efficient.